Coronary microvascular Kv1 channels as regulatory sensors of intracellular pyridine nucleotide redox potential. (9th January 2018) - Dwenger, Marc M.; Ohanyan, Vahagn; Navedo, Manuel F.; Nystoriak, Matthew A.
Abstract: Smooth muscle voltage‐gated potassium (Kv) channels are important regulators of microvascular tone and tissue perfusion. Recent studies indicate that Kv1 channels represent a key component of the physiological coupling between coronary blood flow and myocardial oxygen demand. While the mechanisms by which metabolic changes in the heart are transduced to alter coronary Kv1 channel gating and promote vasodilation are unclear, a growing body of evidence underscores a pivotal role of Kv1 channels in sensing the cellular redox status. Here, we discuss current knowledge of mechanisms of Kv channel redox regulation with respect to pyridine nucleotide modulation of Kv1 function via ancillary Kvβ proteins as well as direct modulation of channel activity via reactive oxygen and nitrogen species. We identify areas of additional research to address the integration of regulatory processes under altered physiological and pathophysiological conditions that may reveal insights into novel treatment strategies for conditions in which the matching of coronary blood supply and myocardial oxygen demand is compromised.